2023
DOI: 10.1021/acs.joc.2c02749
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Friedel–Crafts Alkylation of Indoles with β,γ-Unsaturated α-Ketoesters Catalyzed by New Copper(I) Catalysts

Abstract: New Cu(I) catalysts are effective in enantioselective Friedel–Crafts alkylation of a variety of indoles with different β,γ-unsaturated α-ketoesters. A control study shows that such a catalyst system is less sensitive to air, and the reactions can be carried out without special cares such as glovebox operation or moisture/oxygen-free conditions. Preliminary computation results suggest that there exists π–π stacking between the substrate and the catalyst, and such an interaction seems to play a role in stabilizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…In the case of C11 , nitrogen atom of the proline moieties adopted ( S )‐configuration (denoted as C11 ‐N( S ), Scheme 4). [18] This is also in agreement with our previous X‐ray diffraction result on the similar imidazoline‐containing chiral ligand [17] …”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…In the case of C11 , nitrogen atom of the proline moieties adopted ( S )‐configuration (denoted as C11 ‐N( S ), Scheme 4). [18] This is also in agreement with our previous X‐ray diffraction result on the similar imidazoline‐containing chiral ligand [17] …”
Section: Resultssupporting
confidence: 91%
“…Previously, we found that connecting different proline moieties to binaphthyl skeletons provided chiral ligands which could take the advantages of both the proline moiety and the binaphthol structure. Catalysts bearing binaphthyl-prolinebased tridentate ligands L1-L8 were effective in enantioselective Henry reactions, [12] enantioselective addition of alcohols and t-butyl hydroperoxide to isatin-derived N-Boc ketimines, [13] enantioselective addition of malonates to β,γ-unsaturated αketoesters, [14] and enantioselective Friedel-Crafts alkylation of indoles with β,γ-unsaturated α-ketoesters [15] or isatin-derived N-Boc ketimines. [16] Studies showed that the axial chirality of the binaphthyl skeleton and the central chirality of the proline moiety in these ligands should match with each other, and the substituents R in chiral ligands L1-L8 exhibited drastic effect on the stereofacial selection in asymmetric Henry reaction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…12 This ligand was further found to be effective in the Friedel-Crafts reaction of β,γ-unsaturated α-ketoesters with indoles. 13 In the presence of L7, CuOTf-catalysed reactions gave the desired products in high yields and up to 99% ee. A preliminary study suggested that β,γ-unsaturated α-ketoester bound to the central metal in a mono-dentate way, and the Si-face of the substrate was covered by the chiral ligand, leading to Re-attack products with high enantioselectivity (Fig.…”
Section: Resultsmentioning
confidence: 99%